Prototipe Sistem Kontrol Smart Home Berbasis IoT Dengan Metode MQTT Menggunakan Google Asisstant - Fifit Alfiah; Budi Rahman; Imelda (Ikatan Ahli Informatika Indonesia (IAII), 2020)
The internet of Things for Smart Home is here to offer convenience in controlling electrical devices or lectronic devices remotely by only giving voice commands that have been integrated with Google Assistant services, now traveling home in uncertain times no longer need to worry about turning on or turn off electrical appliances at home with a smart home. The design of this prototype tool implements lights and fans as electrical devices, in making smart home systems require a microcontroller namely the ESP8266 NodeMCU V3 CH340 module as MQTT Broker protocol, IFTTT as a subscriber, and the publisher Google Assistant using MTTQ (Message Queuing Telemetry Transport) method. MQTT used today is using a free cloud server provided by Adafruit. Based on the results of testing the prototype of the IoT-based smart home control system with the MQTT method using google assistant proved that the number of tests for Relay 1, Relay 2 and Relay 3 is six(6), succeeded 5 and failed 1 then the accuracy of success on Relay 1 testing was 88%. Only by giving the command